The influence of the Business Judgment Rule on the accountability of the Board of Directors for their errors or negligence based on Eisenberg's theory of Director's Accountability - Arifin, Miftah; Arifin, Zaenal (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
In the business world, the Business Judgment Rule (BJR) is a legal principle that provides protection to directors when making risky business decisions, as long as those decisions are made in good faith, with sufficient care, and without personal interest. Although BJR is not explicitly regulated in Indonesian law, this principle is reflected in the Limited Liability Company Law and considered in the theory of director liability proposed by Melvin Aron Eisenberg. The purpose of this research is to analyze the application of the Business Judgment Rule principle in Indonesian corporate law to protect directors from liability for their mistakes or negligence, and to evaluate its influence on Eisenberg's theory of director liability. This study uses a normative legal research method that examines legal norms to analyze and interpret legal provisions related to the application of the Business Judgment Rule and director liability in Indonesia, as well as examining the influence of Eisenberg's theory on that doctrine. A conceptual approach is used to study the concept of the Business Judgment Rule and Eisenberg's theory of director liability in depth. The research results show that the Limited Liability Company Law in Indonesia regulates the application of the Business Judgment Rule (BJR), which provides protection to directors from liability for risky business decisions as long as they meet the requirements of good faith, due care, no conflict of interest, and efforts to prevent loss. However, BJR protection is not absolute, and directors can be held accountable if they violate corporate governance principles. Melvin A. Eisenberg's theory of director liability provides clearer boundaries, where directors can lose BJR protection if they violate the duty of care, duty of loyalty, duty of good faith, and duty of candor, making them accountable for their mistakes or negligence in business decision-making.